The Nordic Paradox. Professionals’ Discussions about Gender Equality and Intimate Partner Violence against Women in Sweden - Wemrell, Maria (Women & criminal justice, 2022)
Intimate partner violence against women (IPVAW) is a global public health issue often assumed to be associated with gender inequality. The so-called Nordic Paradox, the apparently contradictory co-existence of high levels of IPVAW and of gender equality in Nordic countries, has not been adequately explained. This study explores discussions about how this apparent paradox can be understood among 30 IPVAW professionals working in southern Sweden, through a thematic analysis of focus groups and individual and paired interviews. The analysis highlights complexities of gender (in)equality and its links with IPVAW in Sweden, of relevance for the addressing and prevention of IPVAW.